FEATURES OF CONSTRUCTION REMOTE SENSING IMAGING SPECTROMETERS FROM SPACE - N. K. Artyukhina; M. N. Kotov (Приборы и методы измерений, 2015)
In article factors influencing quality of the Earth image received with imaging spectrometers are presented: height of an orbit of a spacecraft, atmosphere, characteristics of the optical scheme, type of dispersive element and a photodetector. Results of study of influence of the optical system parameters of a video spectrometer of factors are presented taking into account requirements and restrictions brought by various links of an optoelectronic path of the device.